Lightning Disaster Risk Zoning in Jiangsu Province of China Based on the Analytic Hierarchy Process and Entropy Weight Method - Jin, Chenlu; Shu, Yu; Han, Zhaoquan; Chen, Qu; He, Jing; Wang, Song (Frontiers in Environmental Science, 2022)
Jiangsu Province is located in the middle coastal area of East China, and has a relatively developed economy and a large population density. Severe convection often occurs in Jiangsu Province, and the lightning activities may cause great economic losses and social impact in this region. Based on the theory of natural disaster risk assessment, this study investigates the risk of hazard factors, the sensitivity of hazard-pregnant environment, and the frangibility of a hazard-bearing body in Jiangsu Province. Then, we select thunderstorm days, cloud-to-ground (CG) lightning density, CG lightning current intensity, altitude, topographic relief, soil-electric conductivity, drainage density, population density, gross domestic product (GDP) per land area, and soil utilization type as the influencing factors, and then we use the analytic hierarchy process and entropy weight method to calculate the weights of the influencing factors. Furthermore, all the factors are weighted stacked in ArcGIS, and finally the lightning disaster risk zoning map (1 × 1 km of Jiangsu Province is presented. The results show that the risk of lightning disaster in Jiangsu is low in the north and high in the south. The area of different risk level increases with the decrease in risk level. High-risk areas are mainly in the middle of Nanjing, eastern Changzhou, eastern Wuxi, and the middle of Suzhou. Medium-risk areas are mainly in northern Nanjing, eastern Changzhou, eastern Suzhou, the Tongshan District of Xuzhou City, the Chongchuan District of Nantong City, Lianyun District of Lianyungang City, and the Xiangshui County, Sheyang County, and Dafeng District of Yancheng City. The sub–low-risk areas are mainly in Xuzhou, Suqian, Huai’an, and the middle of Yangzhou City. The low-risk areas are mainly in Lianyungang, Yancheng, northern Nantong, Taizhou, Zhenjiang, southern Nanjing, western Changzhou, western Wuxi, and western Suzhou. We hope this study could provide some references for the lightning disaster prevention and mitigation in Jiangsu Province and East China.